Analysis of DNA Markers from Vietnamese Asarum L. Species - Hue, Huynh Thi Thu; Ky, Le Dinh; Hoang, Nguyen Huy (VNU Journal of Science: Natural Sciences and Technology; Vol 38 No 4, 2022)
The Asarum L. genus includes 128 species with a lot of medicinal effects and has been used extensively in the folk prescriptions for treatment of several diseases such as bronchitis, asthma, rheumatism, and hepatitis. In the world, many researches showed that the Asarum L. species have many kinds of the essential oils such as myristicin, methyl eugenol, myrcene, asafrol, borneol, safrol or α-pinene and substances as secquiterpenes, sterols, naringenin or glycosyl flavonoids. Some reports in Vietnam have been conducted on analyzing secondary compounds of these species. However, it has done a little research on classification of these species through molecular markers. Indeed, the DNA barcoding will help overcome difficulties in recognizing many plants which were endangered species or it is rare materials with high value in medicine. In the study, four DNA barcoding regions - ITS1, ITS2, matK and rpoC were analyzed from some Asarum species that are three species of A. splendens , A. yentuense and A. petelotii . The four barcodes were well amplified by PCR and sequenced by Sanger principal. After that, analyzing sequences showed ITS1, ITS2 had the highest polymorphism, in addition, the markers and matK marker were absolutely suitable for distinguishing the Asarum L. species. The above results are of great significance for the application of the barcodes in the identification of Asarum species, in order to correctly use the medicinal plant sources.